Respiration Effect on Plankton-Oxygen Dynamics in view of non-singular time fractional derivatives - Sekerci, Yadigar; Ozarslan, Ramazan (Elsevier, 2020)
In this work, we investigate a model of oxygen-phytoplankton-zooplankton dynamics with fractional-order derivatives in different types known as the Caputo-Fabrizio and Atangana-Baleanu derivatives, having nonsingular kernels, exponential and Mittag-Leffler. In order to detail the underlying structure of the oxygen-plankton interaction, the model is detailed in analytical and numerical techniques. Hypothetical set of parameters are used in numerical simulations to guarantee that in natural sense, the system in biologically meaningful region. All results obtained are compared with each other under different parameters, and different fractional orders with simulations. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Oxygen; Plankton; Photosynthesis; Caputo-Fabrizio; Atangana-Baleanu; Numerical simulations